Survival analyses of different treatment modalities and clinical stage for hypopharyngeal carcinoma - Lin, Tian-Yun; Lee, Tsung-Lun; Hsu, Yen-Bin; Tai, Shyh-Kuan; Wang, Ling-Wei; Yang, Muh-Hwa; Chu, Pen-Yuan (Frontiers in Oncology, 2023)
Objective: We investigated the effects of different treatment modality and clinical stage for hypopharyngeal carcinoma (HPC) patients. Methods: Between February 2004 and December 2012, 167 HPC patients were reviewed. We calculated overall survival (OS), progression-free survival (PFS), local failure-free survival (LFFS), regional failure-free survival (RFFS), and distant metastasis failure-free survival (DMFFS) using the Kaplan-Meier method and compared various survivals between definitive chemoradiotherapy (CRT) and surgery-based therapy (SBT). Results: There were no significant differences in baseline characteristics between SBT (n=102) and definitive CRT (n=65) groups. The 5-year rates of OS (59.7% vs. 24.0%, P<0.0001) and PFS (49.9% vs. 22.6%, P=0.0002) were significantly better in patients who received SBT than in those who received definitive CRT. SBT group also obtained better LFFS (P<0.0001), RFFS (P=0.0479), and DMFFS (P=0.0110). We did similar analyses by different T-classification (T1-2, T3, and T4) and found that SBT had better OS (P<0.0001 and P=0.0020), PFS (P<0.0001 and P=0.0513), LFFS (P=0.0002 and P=0.0075), RFFS (P=0.1949 and P=0.0826), and DMFFS (P=0.0248 and P=0.0436) in T4 and T1-2 subgroups, but similar OS (P=0.9598), PFS (P=0.5052), RFFS (P=0.9648), and DMFFS (P=0.8239) in T3 patients. Analyses by different overall stage revealed no differences between definitive CRT and SBT for stage III patients but significantly better results for stage IV patients who received SBT. Conclusions: SBT can get significant survival benefits than definitive CRT for the whole cohort patients. Definitive CRT has similar survivals compared with SBT only for T3 tumor or overall stage III disease.